THE EFFECTS OF GROUP WORK ORGANIZATION ON ENHANCING STUDENT INTERACTION IN 2ND YEAR SPEAKING CLASSES IN HONOURS PROGRAM = ẢNH HƯỞNG CỦA VIỆC TỔ CHỨC NHÓM LÊN SỰ TƯƠNG TÁC GIỮA SINH VIÊN TRONG LỚP HỌC KỸ NĂNG NÓI NĂM HAI HỆ CHẤT LƯỢNG CAO - Nguyễn, Mai Quỳnh Trang (2020)
Communicative language teaching and cooperative learning have been widely applied for better teaching and learning results. Group work, in the framework of CLT and cooperative learning, provides numerous benefits. Therefore, it is important for teachers to perform a well-organized group work activity. Group work organization is undeniably a crucial part in every group activity. It affects the application of group activities, group interaction, student engagement as well as speaking performances. Acknowledging its impact, this study aims to investigate both teachers’ and students’ attitudes towards group work organization on enhancing student interaction as well as teachers’ perceptions of its difficulties and effectiveness. Fifty-two students and three teachers in three speaking classes from Honors Program in ULIS participated in the research. They were asked to complete questionnaires and participate in short interviews. Also, observations were later employed to guarantee for better interpretation of the results. Through the application of the study, the researcher found out that teachers and students all acknowledged the importance of group work organization on student interaction in speaking classes. Most students appeared to participate vigorously in speaking activities thanks to the use of group work in general. Nevertheless, when being asked about the effects on student speaking performance, mixed answers were received as students felt confused judging their own performance. Teachers, with years of experience, found it easier to evaluate students speaking performance.